Nurse Workload Against Burnout Syndrome in the Emergency Room - Endah Setianingsih; Nur Wiji Lestari; Barkah Waladani (Urecol Journal. Part C: Health Sciences, 2022)
The Emergency Room is a first aid unit to save lives and prevent death. The high number of visits and the unpredictable condition of patients in the emergency department is one of the stressors. Emergency room nurses have a high risk of fatigue due to work demands and workloads that cause fatigue and boredom. The workload received by nurses is closely related to the level of burnout syndrome. To determine the relationship between workload and burnout syndrome of nurses in the Emergency Room. This study is a quantitative study. The research population was nurses in the emergency room at PKU Muhammadiyah Gombong Hospital. The number of samples used were 27 nurses. Nurses with a heavy workload were 78%, while those with severe burnout were 48%. From the results of the Chi Square test, it was found that the P value of 0.020 workload with burnout syndrome had a significant relationship. There is a significant relationship between workload and burnout syndrome of nurses in the Emergency Room.